The ethical imperatives of the COVID-19 pandemic: A review from data ethics - Arriagada Bruneau, Gabriela (Veritas, 2020)
In this review, we present some ethical imperatives observed in this pandemic from a data ethics perspective. Our exposition connects recurrent ethical problems in the discipline, such as, privacy, surveillance, transparency, accountability, and trust, to broader societal concerns about equality, discrimination, and justice. We acknowledge data ethic’s role as significant to develop technological, inclusive, and pluralist societies.